C-3 Steroidal Hemiesters as Inhibitors of 17β-Hydroxysteroid Dehydrogenase Type 10 - Hanzlova, Michaela; Slavikova, Barbora; Morozovova, Marina; Musilek, Kamil; Rotterova, Aneta; Zemanová, Lucie; Kudova, Eva (ACS omega, 2024)
17β-HSD10 is a mitochondrial enzyme that catalyzes the steroidal oxidation of a hydroxy group to a keto group and, thus, is involved in maintaining steroid homeostasis. The druggability of 17β-HSD10 is related to potential treatment for neurodegenerative diseases, for example, Alzheimer's disease or cancer. Herein, steroidal derivatives with an acidic hemiester substituent at position C-3 on the skeleton were designed, synthesized, and evaluated by using pure recombinant 17β-HSD10 converting 17β-estradiol to estrone. Compounds 22 (IC50 = 6.95 ± 0.35 μM) and 23 (IC50 = 5.59 ± 0.25 μM) were identified as the most potent inhibitors from the series. Compound 23 inhibited 17β-HSD10 activity regardless of the substrate. It was found not cytotoxic toward the HEK-293 cell line and able to inhibit 17β-HSD10 activity also in the cellular environment. Together, these findings support steroidal compounds as promising candidates for further development as 17β-HSD10 inhibitors.